2016
DOI: 10.1111/clr.12996
|View full text |Cite
|
Sign up to set email alerts
|

The influence of collagen membrane and autogenous bone chips on bone augmentation in the anterior maxilla: a preclinical study

Abstract: The addition of autogenous bone chips and the presence of the collagen membrane increased bone formation around DBBM particles. Wound protection from mechanical noxa during early healing may be critical for bone formation within the grafted area.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
35
0
3

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(45 citation statements)
references
References 47 publications
7
35
0
3
Order By: Relevance
“…32 Deproteinized bovine bone mineral is a natural, nonantigenic, porous bone mineral matrix produced by removing all organic components from bovine bone. 39,40 However, the analysis of fluorochrome labeling at 4week intervals (Figure 4) and the result of histological examination (Figure 5) in this study indicated that even with the CM, the slow degradation of DBBM does not offer enough space, and hinder the new bone growth over 12-week period. 33 Deproteinized bovine bone mineral was selected in our study because it has been widely used in the oral and maxillofacial practice, and has shown satisfactory results.…”
Section: Main Findingsmentioning
confidence: 61%
See 2 more Smart Citations
“…32 Deproteinized bovine bone mineral is a natural, nonantigenic, porous bone mineral matrix produced by removing all organic components from bovine bone. 39,40 However, the analysis of fluorochrome labeling at 4week intervals (Figure 4) and the result of histological examination (Figure 5) in this study indicated that even with the CM, the slow degradation of DBBM does not offer enough space, and hinder the new bone growth over 12-week period. 33 Deproteinized bovine bone mineral was selected in our study because it has been widely used in the oral and maxillofacial practice, and has shown satisfactory results.…”
Section: Main Findingsmentioning
confidence: 61%
“…The addition of CM has been proved to be effective in increasing new bone formation. 39,40 However, the analysis of fluorochrome labeling at 4week intervals (Figure 4) and the result of histological examination (Figure 5) in this study indicated that even with the CM, the slow degradation of DBBM does not offer enough space, and hinder the new bone growth over 12-week period. This was in agreement with the findings of 2 former studies.…”
Section: Main Findingsmentioning
confidence: 61%
See 1 more Smart Citation
“…1,19,20 Cortical blocks were then shaped on the alveolar bone defects to obtain the maximum contact surface between grafts and the recipient site, promoting the integration process 21 ( Figure 5). 23 Periosteal incisions were performed prior to wound closure to release flaps, allowing for tension-free suturing. Cancellous bone chips were used to fill gaps between grafts and the receiving bone walls.…”
Section: Surgical Procedures: Calvarial Graftsmentioning
confidence: 99%
“…Cancellous bone chips were used to fill gaps between grafts and the receiving bone walls. 23 Periosteal incisions were performed prior to wound closure to release flaps, allowing for tension-free suturing.…”
Section: Surgical Procedures: Calvarial Graftsmentioning
confidence: 99%